2001
DOI: 10.1016/s0042-6989(01)00105-5
|View full text |Cite
|
Sign up to set email alerts
|

Surface color from boundaries: a new ‘watercolor’ illusion

Abstract: A colored line flanking a darker border will appear to assimilate its color onto the enclosed white area over distances of up to 45 deg (the Watercolor Effect). This coloration is uniform and complete within 100 ms. We found that thin (6 arcmin), winding inducing lines with different contrasts to the ground are generally more effective than thick, straight, and equiluminant lines. Blue and red lines induce the strongest effects, but watercolor spreading may also be seen with green and yellow. On a white backgr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
244
3
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 212 publications
(265 citation statements)
references
References 25 publications
17
244
3
1
Order By: Relevance
“…Others have argued against a substantial contribution of aberration (Fach and Sharpe 1986;Moulden et al 1993). This difference is reflected in studies suggesting that assimilation is present (Pinna et al 2001;Monnier and Shevell 2003) or absent (Broerse et al 1999) depending on whether or not stimuli were observed through an achromatizing lens. Our data show that chromatic aberration cannot account for the WCE in the wider stimuli that have been used in previously published work.…”
Section: The Role Of Chromatic Aberration In Color Assimilationmentioning
confidence: 99%
See 1 more Smart Citation
“…Others have argued against a substantial contribution of aberration (Fach and Sharpe 1986;Moulden et al 1993). This difference is reflected in studies suggesting that assimilation is present (Pinna et al 2001;Monnier and Shevell 2003) or absent (Broerse et al 1999) depending on whether or not stimuli were observed through an achromatizing lens. Our data show that chromatic aberration cannot account for the WCE in the wider stimuli that have been used in previously published work.…”
Section: The Role Of Chromatic Aberration In Color Assimilationmentioning
confidence: 99%
“…Pinna et al (2001) pointed out that the induced color in the WCE continues to be seen up to about 45 deg. Our results show that with large stimuli the effect is present with an achromatizing lens.…”
Section: The Role Of Chromatic Aberration In Color Assimilationmentioning
confidence: 99%
“…Illusions such as neon color spreading and the water-color illusion (da Pos & Bressan, 2003;Pinna, Brelstaff, & Spillmann, 2001) have been taken as direct evidence of filling-in. Filling-in processes have also been invoked to explain a variety of other percepts, including brightness perception (Grossberg & Todorović, 1988;Todorović, 1987), properties of McCollough afterimages (Broerse, Vladusich, & O'Shea, 1999;Grossberg, Hwang, & Mingolla, 2002), properties of color complement afterimages (Shimojo, Kamitani, & Nishida, 2001), and some aspects of 3-D perception (Grossberg, 1997).…”
mentioning
confidence: 99%
“…One trick, for example, creates illusory colors by rapidly flickering specially configured achromatic contours (see, e.g., Benham, 1894), and another creates illusory colors within the uncolored interior of a figure defined by chromatic boundaries (see, e.g., Pinna, Brelstaff, & Spillmann, 2001). While fascinating in their own right, illusory colors also offer an effective means for dissociating physical stimulation from perceptual experience.…”
Section: Discussionmentioning
confidence: 99%